Wave emission from an open-ended cylindrical channel in a cold magnetoplasma. - Kudrin, A.V.
We study wave emission from a transmitting system consisting of a magnetic-field-aligned cylindrical plasma channel of enhanced density and a loop antenna immersed in it. An ambient medium is assumed to be a cold uniform magnetoplasma. It is found that when the plasma density in the near-antenna zone increases, the total power radiated from the antenna increases considerably due to the efficient excitation of guided modes on the channel. We consider the emission of these modes from the channel end, assuming that the plasma density in the channel decreases gradually with distance from the loop. It is shown that under ionospheric conditions this transmitting system can be useful for improving the antenna coupling to VLF waves of the ambient plasma
Keywords: VLF satellite transmitting systems; VLF waves; Ambient plasma; Antenna coupling; Cold magnetoplasma; Cold uniform magnetoplasma; Guided modes excitation; Ionospheric conditions; Loop antenna; Magnetic-field-aligned cylindrical plasma channel; Near-antenna zone; Open-ended cylindrical channel; Plasma density; Total radiated power; Transmitting system; Wave emission